Snail 3G: genomics, genetics, and gene-editing of Biomphalaria glabrata - Zhang, Si-Ming (Frontiers in Genetics, 2026)
This review highlights recent advances and ongoing challenges in the genomics, genetics, and gene-editing (3G) of the freshwater snail Biomphalaria glabrata, based on insights gained from a novel model system we initiated two decades ago. B. glabrata is an intermediate host of the human blood fluke Schistosoma mansoni and serves as the principal model organism for schistosomiasis research. We developed two homozygous lines of B. glabrata, the iM line and iBS90, through 81 and 41 generations of selfing the commonly used M line and BS90, respectively. These lines display contrasting infection phenotypes: susceptibility or resistance to S. mansoni. High-quality scaffold-based genome assemblies were generated for both lines, followed by a chromosome-level assembly of the iM line genome. An F2 segregating population derived from these lines enabled the identification of three loci, two linked to resistance or susceptibility and one associated with pigmentation, using a double digest restriction-site associated DNA sequencing (ddRADseq) approach. Recombinant inbred lines (RILs) were developed through two crosses and ten generations of selfing. Genetic mapping with RILs refined the resistance locus on chromosome 5 from 8 to 3 Mb through individual-based whole-genome sequencing. Ongoing work includes comparative transcriptome analyses of the two homozygous lines and RILs in response to schistosome infection, along with fine-scale mapping of advanced intercross lines to elucidate the molecular basis of the snail’s anti-schistosome defenses. Over the past 10 years, we have made extensive efforts to achieve germline delivery and generate genetically modified snails. Although pantropic lentiviral and yolk protein–mediated germline delivery methods were unsuccessful, these pioneering experiments provide valuable insights for future research. Finally, we successfully generated germline-edited B. glabrata, the first genetically modified schistosomiasis vector snail, by microinjecting CRISPR/Cas9 and guide RNA (gRNA) targeting the fibrinogen-related protein 3.1 (FREP3.1) gene into decapsulated embryos, followed by ex ovo culture. This breakthrough establishes a foundation for innovative genetic strategies to control this neglected tropical disease.